The Emergence of Rice-based Cropping Pattern After Green Revolution in Haryana: Some Aspects of Growth and Distribution - Dr. Vinod Kumar (Innovative Research Thoughts, 2023)
Rice is the staple food for about 60 percent of the total population of the country. Cultivation of the Paddy requires special geo-climatic conditions, and in most of the area, paddy cultivation is limited by rainfall and temperature. The crop required in most instances a relatively high atmospheric humidity, an average temperature of 20° centigrade, and a well-distributed rainfall between 125 centimeters and 150 centimeters during the growing season. To the climatic requirement must also be added an abundant supply of fresh water for irrigation where the rainfall is less than 125 centimeters. Rice thrives well on a variety of soils widely ranging from slightly acidic to slightly alkaline particularly the heavy, compact, and acidic soils having the ability to hold water over the surface for a considerable period. Haryana is a traditionally wheat-producing region but the enterprising farmers of the plain have made full use of package technology including perennial irrigation by canals and tube wells, HYV seeds, and fertilizers. This has resulted in a widespread change in the cropping pattern of the state and the region has become a very important producer of rice. Over a short period, the spread of rice cultivation has enabled this region to occupy an important place among the rice-producing states of India. The area used for the cultivation of paddy, a highly water-intensive crop, has increased fourfold. In 1960-61 area under rice constituted only 3.8 percent ofthe total cropped area increased to 23.37 percent in 2020-21.